Campaign Props: The Environmental Threat Behind Indonesia's Democratic Celebration - Waluyo, Bambang Dwi; Chandrabuwono, Achmad Bayu (Jogjakarta Communication Conference (JCC), 2024)
Campaigns in general elections have become a very important part of the implementation of democracy in a country. Indonesia as one of the democratic countries is also inseparable from these activities as part of the culture of democracy. However, the implementation of the campaign itself varies in every democratic country. The implementation of the 2024 elections in Indonesia, especially the Banjarmasin city area, is colored with banners, banners and billboards installed throughout the country. However, the installation of banners and billboards, especially those in the Banjarmasin city area, is still mounted on trees, corners, empty houses, in front of alleys and electric poles. Therefore, this paper raises the research question of how the use of billboards as promotional media in elections can disrupt the environment. Using qualitative methods, data was collected through literature study, documentation and direct observation. Through this research, it can be understood that the use of billboards on trees and public facilities is disruptive as a medium that is not environmentally friendly.